ASUPAN KALSIUM, STATUS GIZI, TEKANAN DARAH DAN HUBUNGANNYA DENGAN KELUHAN SENDI LANSIA DI PANTI WERDHA BANDUNG - Nining Tyas Triatmaja; Ali Khomsan; Mira Dewi (Food and Nutrition Society of Indonesia, 2013)
The objective of this study was to determine the relationship of calcium intake, nutritional status, and blood pressure to joint pain among elderly in nursing homes in Bandung. The study design was cross-sectional study. Subjects were consisted of 12 elderly men and 69 elderly women from four nursing homes in Bandung. Most subjects had joint pain (59.3%), hypertension (30.9%), and were overweight (39.5%). There was no significant relationship between frequency of consumption of calcium food sources and nutritional status, blood pressure, joint pain, and the level of joint pain (p>0.05). There was no significant relationship between joint pain and the level of joint pain with blood pressure and nutritional status.